"Natural Evaporation from Open Water, Bare Soil and Grass" by Harold L. Penman, Proceedings of the Royal Society of London (1948) A193:120–146. Issue 6 (1st November 2019) - Sinclair, Thomas R.
ABSTRACT: This article is part of a series of brief commentaries to highlight papers that have resulted in important and distinctly new perspectives in crop science. A criterion for selection of papers is that they must have been published at least 20 yr ago to allow for a long‐range perspective in assessment of the papers. The current article briefly reviews the paper by Harold L. Penman published in 1948 that offered an original analysis of approaches to estimate evaporation from natural surfaces. He developed two approaches: one based on a sink strength model, and the second on an energy balance model. He compared the predictions of these approaches to his experimental observations of evaporation from open water, bare soil, and grass. He found each of the models did well ( r ≈ 0.8) in predicting open water evaporation. The evaporation from bare soil and grass was less than that from the open water, and the predicted evaporation amounts were variable even when normalized by open water evaporation. Even though Penman warned that aspects of the approaches were empirical, the energy balance model remains a mainstay in predicting crop water loss.